Treatment of myeloid neoplasia with doxorubicin and cytarabine in 11 dogs. (7th October 2022) - Matsuyama, Arata; Beeler‐Marfisi, Janet; Wood, R. Darren; Richardson, Danielle; Calvalido, Jerome; Mutsaers, Anthony J.; Bienzle, Dorothee
Abstract: Myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML) are primary myeloid neoplasms in dogs generally considered to have a poor outcome. In this study, we assessed toxicity, efficacy and outcome of concurrent administration of doxorubicin and cytarabine in 11 dogs with myeloid neoplasia. Bone marrow specimens were reviewed by three pathologists and classified as either MDS ( n = 2), high grade MDS/early AML (MDS/AML; n = 4) or AML ( n = 5). The median number of treatment cycles was 5 (range 1–9) and resolution of cytopenia was reported in 7 of 11 dogs including 2 dogs with MDS, 2 dogs with MDS/AML, and 3 dogs with AML. The median duration of remission in the seven responders was 344 days (range 109–1428) and the median overall survival for all dogs was 369 days. Adverse events consisted of predominantly low‐grade gastrointestinal illness and myelosuppression. Three dogs developed grade V toxicity manifesting with heart failure ( n = 2) at 369 and 1170 days after diagnosis and acute gastrointestinal side effects ( n =1) . Despite a limited sample size, these results suggest that a doxorubicin and cytarabine protocol may be considered as a therapeutic option in dogs with myeloid neoplasia. Protocol safety, in particular regarding myocardial toxicity, and efficacy should be further investigated.